CONVERSION OF SPEECH EXPRESSIONS INTO UNITS REPRESENTING METAPHOR, METONYMY, SIMILE AND IRONY IN TRANSLATION - Rakhimova Irodakhon Bahodirovna (American Journals, 2024)
Translation is one of the most ancient types of human activity, aimed at the implementation of communication between peoples with different languages. In the componential structure of the translation, attention should be paid to the following features of the original source text: a) sequence of narration; b) the order of individual sections in the text does not change. The aim of these is to ensure that each part of the translation is as similar as possible to its corresponding part in the original, and any deviation from uniformity is the result of the need to more accurately convey the meaning reflected in the original.
Keywords: functional status of translation, means of artistic image expression, metaphor, metonymy, irony.